PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS MOBILE PADA MATA PELAJARAN INFORMATIKA DI SMK NEGERI I KOTO XI TARUSAN - Mahrifah, Ega; Rini, Faiza; Pratama, Ade (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
The development of mobile-based interactive learning media in informatics subjects at SMK Negeri I Koto The aim of this research is to develop valid and practical mobile-based interactive learning media. This research uses the Research and Development (RD) method with the ADDIE development model, namely Analysis, Design, Development, Implementation, and evaluation. The instruments used in this research were media validity questionnaire sheets, material validity questionnaire sheets, teacher practicality questionnaire sheets and student practicality questionnaire sheets. The research subjects in this study were the media validity of 2 lecturers at PGRI University of West Sumatra, the material validity of 2 teachers, the practicality of 1 informatics teacher and 53 class X RPL students at SMKN I Koto XI Tarusan.The results of this research show that the average value of the media validity test is 74,99% in the very valid category, material validity is 72,91% in the very valid category, teacher practicality is 77,77% in the very practical category, and student practicality in class X RPL 1 is 81,75%, RPL 2 is 85,29% in the very practical category. Thus, it can be concluded from the data obtained that mobile-based interactive learning media in informatics subjects is feasible and practical to use in the learning process.